Diversificação evolutiva de gobídeos no litoral brasileiro: padrões citogenéticos e ecomorfológicos - Lima Filho, Paulo Augusto de (2011)
The fishes of the order Perciformes are characterized as an important model for understanding the genetic structure of marine populations, because besides they present examples of conservation chromosomal, also they present the karyotype diversification for some groups. Gobiidae family is the most specious in the marine environment. Among its representatives, many species are part of a cryptic fauna little noticed and studied, a wide distribution with behavioral and reproductive characteristics, that make them conducive to the action of biogeographical barriers. Morphologically this family presents reduced body structures through simplification and regressions. Despite their importance in evolutionary inferences, cytogenetics data are incipient facing their species diversity, especially with western Atlantic species. In order to estimate the evolutionary diversity in Gobiidae, it were developed cytogenetic analysis and the standards body, through geometric morphometrics in five species on the Brazilian coast, Coryphopterus glaucofraenum, Bathygobius mystacium, B. soporator, Ctenogobius smaragdus e C. Boleosoma. The data show significant karyotype and morphological diversity among the species. The pericentric inversions and mergers play an important role in chromosomal evolution of this family, causing karyotypic structural and numerical differences in all species. Karyotypic and morphological comparisons among geographic samples of B. soporator from the coast of Maranhão, Rio Grande do Norte and Bahia showed cytogenetics patterns commons, but different morphological patterns. A sample from the Atol das Rocas revealed conspicuous morphological and karyotypic differentiation of another continental populations, confirming the presence of a new island species. The approaches done reveal diversification consistent with characteristics of a group of low vagile and largely able to environmental selection due from peculiar ecological requirements